Essential Oils Antagonism Against Three Hygiene Significant Yeasts and Juice Spoilage by Saccharomyces Cerevisiae - Sahar, Yassin Ibrahim (Journal of Human Health Research, 2017)
Antifungal antagonism of different fourteen plant essential oils was examined as natural agents against economic and hygienic effective three yeasts; the preservative efficacy of most potent anti-yeast essential oil in food sanitary was also tested. Study involved oils antifungal bioactivity screening against Saccharomycescerevisiae, Candida albicans,and Candida utilis. Study also included selection and invitro extraction of most bioactive oil, and evaluation of its antifungal minimal inhibitory concentrations (MICs). Control ofjuice spoilage by Saccharomycescerevisiae under the effect of in vitro oil extract different concentrations was also screened. Among the tested essential oils, apricot seed oil was the most bioactive anti-yeast agent. Two MIC values of apricot oil invitro extract, 12.5μgml-1 and 25μgml-1 were recorded. In juice samples, oil extract bioactivity increased gradually up to concentration 100μgml-1.Highest oil preservative ability was observed at oil concentration of and above 125μgml-1. Higher oil concentrations needed for juice preservation were found more than in vitro assay to give the same effect. Applying of apricot oil and some other plant essential oils could be used as an environmental safety mode in osmophilic food preservation and in Candidate diseases biocontrol.
Keywords: essential oils; antagonism; antifungal; food spoilage; osmophilic; apricot; Saccharomyces; Candida.